EFFECT ON WEED SPECIES FROM MECHANICAL AND CHEMICAL CONTROL IN SUGAR BEET (BETA VULGARIS L.) IN THE TRANSYLVANIAN DEPRESION - Sergiu Cioca Parasca; Teodor Rusu; Ileana Bogdan (Agricultura, 2025)
The research investigate the effectiveness from mechanical and chemical control, on the weed species in sugar beet from three agricultural years (2021-2023) including the sensor guided hoe in the Transilvanyan Depresion. Weed control strategies are made strictly chemical with spraying herbicides mixes at several timings in the early growth stage of sugar beet. Precision agriculture including camera recognizing cultivation row and hydraulic steering are used often. Examinating the combinations of the chemical and mechanical weed control in sugar beet, measuring the effects on weed species in four different experimental plots. Data analysis is collected for weed species with two passes involving mechanical control in stage of BBCH 19 and BBCH 31, including the sensor-based hoe set up and herbicide aplications. Results show that is possible to reduce herbicides but not replace them entirely in sugar beet and you can achieve a wider weed management on species.